Sentinels guarding the grail: Value-added measurement and the quest for education reform - Gabriel, Rachael; Lester, Jessica Nina (Education Policy Analysis Archives, 2013)
Over the past three years, Value-Added Measurement (VAM) has captured the attention of the American public through high-profile media representations of the tool and the controversy that surrounds it. In this paper, we build upon investigations of constructions of VAM in the media and present a discourse analysis of the policymaking process within the meetings of Tennessee’s Teacher Evaluation Advisory Committee (TEAC), a 15-member panel appointed by the Tennessee governor to develop a new teacher evaluation policy under Race to the Top. The data included audiorecordings of public meetings from March, 2010 through the end of the committee’s work in April, 2011. As we analyzed the talk of the TEAC, we oriented to the particular version of VAM worked up within these conversations in relation to a descriptive metaphor in which VAM is compared to a “sentinel of trust.” We present examples to illustrate three patterns in the construction of VAM as the sentinel of trust within teacher evaluation: (1) VAM alone defines effectiveness; (2) VAM is the only objective option; and (3) concerns about VAM are minimized. We discuss the implications of this way of thinking and talking about VAM and contrast it with other possibilities, including those constructed by teachers, researchers, and the media.